Financial Strategies and Behavioral Insights: Navigating Modern Finance in a Digital Era - Wulandari, Anis; Barlian, Barin; Yuniar, Evilia Sri; Kusumawati, Fariyana; Soejono, Fransiska; Irawan, Irly Artiara; Sintha Trisnayuni, Komang Ayu; Oktaviani, Ni Kadek; Sekar Wangi, Ni Luh Ayu; Ayu Suryandari, Ni Nyoman; Oktaviani, Nita Fauziah; Kompyurini, Nurul; Sulastri, Sulastri; Sambharakreshna, Yudhanta (AIBPM Publisher, 2026)
The insights shared in this book reflect the evolving challenges and dynamic innovations in the world of finance and business. This book offers a blend of theoretical frameworks and practical implementations that will benefit researchers, students, and professionals alike. I commend the authors and editors for their dedication in compiling such a comprehensive and timely work